Impact of an Integrated Scientific Moral Values Instructional Approach on the Improvement of the Elementary School Students’ Moral Character - Sri Saparahayuningsih (Universitas Bengkulu, 2019)
The purpose of this research is to know the impact of the implementation of an integrated moral-values instructional approach on the development of the elementary school students' moral character. The research was conducted in the form of a test-retest experiment. The results of this research showed that the implementation of the integrated scientific moral-values instructional approach on an instructional process of social studies is able to increase 67% of the improvement the moral- characters compared to the implementation scientific approach contained in the content of social studies to the student intact. The instructional approach is very effective to develop students’ moral-characters.